2017
DOI: 10.1002/2327-6924.12446
|View full text |Cite
|
Sign up to set email alerts
|

Improving prescribing practices

Abstract: Background and purpose To assess impact of a pharmacist‐led educational intervention on family nurse practitioner (FNP) students’ prescribing skills, perception of preparedness to prescribe, and perception of pharmacist as collaborator. Method Prospective pre–post assessment of a 14‐week educational intervention in an FNP program in the spring semester of 2014. Students participated in an online module of weekly patient cases and prescriptions emphasizing legal requirements, prescription accuracy, and appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The highest level of evidence (Level IV) was generated from 10 secondary analyses of service use and expenditure/billing data studies with a health economic focus [ 10 , 11 , 27 34 ], and one pre-test, post-test study [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest level of evidence (Level IV) was generated from 10 secondary analyses of service use and expenditure/billing data studies with a health economic focus [ 10 , 11 , 27 34 ], and one pre-test, post-test study [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies examined the benefits of multidisciplinary education for primary care NPs, finding an improvement in self-efficacy was statistically significant for NPs who completed an interprofessional program with dental students compared with non-participants ( p = 0.02) [ 73 ]. A 14-week multidisciplinary pharmacy led program improved Family NPs’ recognition and avoidance of medication errors, although overall competency was not statistically improved [ 35 ]. Virtual programs for rural primary care NP candidates [ 74 , 75 ] reported participant satisfaction with virtual education, simulation and evaluation of core clinical skills in primary care, however these two studies reported incomplete methodology.…”
Section: Resultsmentioning
confidence: 99%